Nuclear magnetic resonance metabolic fingerprint of bevacizumab in mutant IDH1 glioma cells - Mesti, Tanja (Radiology and oncology (Ljubljana), 2018)
Malignant gliomas are rapidly growing tumours that extensively invade the brain and have bad prognosis. Our study was performed to assess the metabolic effects of bevacizumab on the glioma cells carrying the IDH1 mutation, a mutation, associated with better prognosis and treatment outcome. Bevacizumab is known to inhibit tumour growth by neutralizing the biological activity of vascular endothelial growth factor (VEGF). However, the direct effects of bevacizumab on tumour cells metabolism remain poorly known. Materials and methods The immunoassay and MTT assay were used to assess the concentration of secreted VEGF and cell viability after bevacizumab exposure. Metabolomic studies on cells were performed using high resolution magic angle spinning spectroscopy (HRMAS). Results mIDH1-U87 cells secreted VEGF (13 ng/mL). Regardless, bevacizumab had no cytotoxic effect, even after a 72h exposure and with doses as high as 1 mg/mL. Yet, HRMAS analysis showed a significant effect of bevacizumab (0.1 mg/mL) on the metabolic phenotype of mIDH1-U87 cells with elevation of 2-hydroxyglutarate and changes in glutamine group metabolites (alanine, glutamate, glycine) and lipids (polyunsaturated fatty acids PUFA, glycerophosphocholine, and phosphocholine). Conclusions In mIDH1-U87 cells, changes in glutamine group metabolites and lipids were identified as metabolic markers of bevacizumab treatment. These data support the possibility of a functional tricarboxylic acid cycle that runs in reductive manner, as a probable mechanism of action of bevacizumab in IDH1 mutated gliomas and propose a new target pathway for effective treatment of malignant gliomas.
Keywords: bevacizumab; celični metabolizem; maligni gliom; metabolni odtis; mutacija IDH1